Tin(ii)-functionalization of the archetypal P8W48 polyoxotungstate. Issue 44 (21st October 2015) - Izarova, N. V.; Klaß, L.; de Oliveira, P.; Mbomekalle, I.-M.; Peters, V.; Haarmann, F.; Kögerler, P.
Abstract : The synthesis of SnII8P8 W48 , the first example of the archetypal P8 W48 -type polyoxotungstate cluster functionalized with the main group metal ions, elucidates the critical reaction parameters that have to be adjusted to avoid numerous competing side reactions. Abstract : The synthesis of [K4.5 ⊂ (ClSn II )8 P8 W48 O184 ] 17.5−, featuring Sn(ii ) ions in trigonal-pyramidal SnO2 Cl environment coordinating to the two inner rims of the wheel-shaped P8 W48 -type polyoxotungstate(vi ) archetype, showcases how high chloride ligand concentrations as well as the control of the polyanion solubility via electrolytes and evaporation rates are essential to prevent numerous competing reactions that can hamper the Sn(ii ) functionalization of polyoxometalates.